Implementasi Pendidikan Multikultural dalam Mencengah Bullying - Feri Padli; Siti Raodhatul Ummah; Rusdi Rusdi; Abdul Mannan (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
The diversity of cultures, tribes, races, religions, characters, and backgrounds in schools is the potential for differences in behavior, attitudes, or opinions. Meanwhile, students have the freedom to interact with peers. Supervision cannot be carried out continuously by the school. Every interaction between students, that's when bullying usually happens with each other. This action can occur between individuals, individuals with groups, groups with groups, and so on. Lack of understanding among students so this behavior continues to occur repeatedly. The lack of effort made coupled with habits that are difficult to change. Therefore, strong efforts are needed to minimize bullying. This article provides solutions for handling bullying in the school environment by involving various policymakers. From the results of the study, it was determined that Multicultural Education can be implemented at every level of education. The curriculum is regulated by requiring multicultural lessons to be required. The goal is to provide understanding as well as the practice of mutual respect for fellow human beings. Maximizing education about forms of bullying will reduce their actions. Students will consciously understand each other better and understand that the behavior can harm others.